Exploring the use of humour in medical education in the GP small group setting. Issue 6 (2nd November 2018) - Edwards, Emily
ABSTRACT: This report summaries work from a dissertation project which critically examines the uses of humour in the GP small group learning environment, via a qualitative enquiry approach. Humour is widely used in medical education, though conclusions from literature are ambiguous and rarely field-focused. The aims of my enquiry were to observe the types of humour used and explore the impact these have, with a focus on the 'curriculum in action'. I used two data collection methods including a group observation as a non-participant and a focus group discussion with trainees. Findings support the use of appropriate humour by trainees and facilitator to promote learning, including self-depreciating and dark humour. I propose that educators should be confident in using humour and brave in exploring new humour approaches and modalities, such as medical improvisation and the humanities.